Acidic liquid-swollen polymer membranes exhibiting anhydrous proton conductivity higher than 100 mS cm−1 at around 100 °C. Issue 26 (3rd May 2019) - Kajita, Takato; Tanaka, Haruka; Noro, Atsushi; Matsushita, Yushu; Nakamura, Naoki
Abstract : Anhydrous proton-conductive membranes are prepared by swelling cross-linked flexible basic polymers with a large amount of H2 SO4 via ionic interaction. Abstract : Anhydrous proton-conductive membranes are prepared by incorporating sulfuric acid (H2 SO4 ) into cross-linked poly(4-vinylpyridine) (CL-P), where H2 SO4 mixes CL-P homogeneously at the molecular level, and therefore incorporated H2 SO4 does not leach out from CL-P, even when the weight ratio of H2 SO4 to CL-P is about four. The membranes are soft but self-standing and exhibit anhydrous conductivity higher than 100 mS cm −1 at around 100 °C. Furthermore, a membrane composed of polystyrene- b -poly(4-vinylpyridine)- b -polystyrene triblock copolymers and H2 SO4 achieves not only high anhydrous conductivity but also good mechanical properties as a membrane.